Transcutaneous measurement of hyperbilirubinaemia: comparison of the Minolta jaundice meter and the Ingram icterometer - BEKİROĞLU, GÜLNAZ NURAL; BİLGEN, HÜLYA SELVA (CARFAX PUBL CO, 1998)
The effectiveness of two different non-invasive transcutaneous bilirubin measurement devices was compared with serum bilirubin levels in 96 healthy newborns. Transcutaneous measurements were obtained with the Minolta Air Shields jaundice meter and the Ingram icterometer and serum bilirubin levels were determined by a direct spectrophotometric method (Bilitron 444). A linear correlation existed between serum bilirubin values and the readings on both the Minolta jaundice meter (r= 0.83) and the Ingram icterometer (r = 0.78). The Kappa coefficient was 0.66. The sensitivity, specificity and positive and negative predictive values were 100%, 56%, 33% and 100% for the Minolta jaundice meter and 100%, 48%, 29% and 100% for the Ingram icterometer, respectively. The high sensitivity and negative predictive value of both devices render them suitable for screening neonatal hyperbilirubinaemia. However, because of its low cost, the Ingram icterometer is preferable to the more complex and expensive Minolta jaundice meter, especially in countries with a high birth rate, such as Turkey.
Keywords: TRANS-CUTANEOUS BILIRUBINOMETRY; TERM INFANTS